EDUCATION FOR NURSES WORKING IN PRE-HOSPITAL EMERGENCY CARE - Suroso, Heri; Fajriyah, Novita; Susila, Wahyu Dini Candra; Qomariah, Siti Nur (SYNTHESIS Global Health Journal, 2023)
Background. Pre-hospital emergency care is the most important part of ambulance services that provide emergency health services in providing an assessment of the patient's condition and providing intervention measures quickly and appropriately to prevent delays in handling patients before arriving at the hospital. A systematic review aims to find out the education for nurses working in ambulances (pre-hospital). Research Method. Systematic review goes through several stages, namely making questions, identification, eligibility, selection of article inclusion, screening, and assessment/appraisal. The Selection Process is listed in the thematic review framework and the results of 9 articles are obtained. Articles are then summarized and assessed JBI on each of the articles Findings. The data showed varying results adapted to the system and the conditions from which the study was conducted. To improve the knowledge, skills, and experience of nurses, nurses who work in ambulances (pre-hospital), are carried out to provide education with 3 methods, such as providing questionnaires, simulations and relationships between nurses and patients through 4-phase identification. Conclusion. An effort to improve the knowledge, skills, and experience of nurses working in the ministry is to apply several special education and training methods for ambulance nurses such as providing questionnaires, simulations and and relationships between nurses and patients through four phases, namely orientation, identification, exploitation and resolution.